A comprehensive study of geothermal heating and cooling systems. (January 2019) - Soltani, M.; M. Kashkooli, Farshad; Dehghani-Sanij, A.R.; Kazemi, A.R.; Bordbar, N.; Farshchi, M.J.; Elmi, M.; Gharali, K.; B. Dusseault, Maurice
Highlights: Comprehensive investigation of the geothermal heating and cooling systems. Recognition and accommodation of factors that can enhance installation soundness of geothermal heating or cooling systems. Overview of GSHPs and GHEs in the geothermal heating and cooling systems. Abstract: Geothermal heat is an energy source that is local, reliable, resilient, environmentally-friendly, and sustainable. This natural energy is produced from the heat within the earth, and has different applications, such as heating and cooling of buildings, generating electricity, providing warm/cold water for agricultural products in greenhouses, and balneological use. Geothermal energy is not dependent on weather or climate and can supply heat and electricity almost continuously throughout the year. It may even be possible to use geothermal projects as "thermal batteries", wherein waste or collected heat is stored for future use, even seasonal use, making geothermal energy "renewable" at a time scale of years. Extensive research has been carried out on different technologies and applications of geothermal energy, but comprehensive assessment of geothermal heating and cooling systems is relevant because of changing understanding, scale of application, and technology evolution. This study presents a general overview of geothermal heating and cooling systems. We provide an introduction to energy and the environment as well as the relationship between them; a brief history of geothermal energy; a discussion of district energy systems; a review of geothermal heating and cooling systems; a survey of geothermal energy distribution systems; an overview of ground source heat pumps; and, a discussion of ground heat exchangers. Recognition and accommodation of several factors addressed and discussed in our review will enhance the design and implementation of any geothermal heating or cooling system.